PENGARUH MULTINATIONAL COMPANY DAN INTENSITAS ASET TETAP TERHADAP TAX AVOIDANCE (Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2021) - Nina Nursida; Yolanda Pratami (Yayasan Azam Insan Cendikia, 2022)
This study aims to empirically examine the effect of Multinational Companies and Fixed Assets Intensity on Tax Avoidance in Manufactures and Beverages Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2020-2021. This study is a quantitative study which was analyzed using multiple regression analysis method with the help of SPSS 26. Through purposive sampling technique, from the total population obtained by 29 companies, 20 companies met the criteria as samples. The results showed that Multinational Companies had no significant effect on tax avoidance, and Fixed Asset Intensity had a significant effect on tax avoidance.